An improved carrier-phase-based method for precise time synchronization using the observations from the China Space Station-ground synchronization system - Yanming Guo; Zhibing Pan; Xuewen Gong; Shuaihe Gao; Pei Wang; Yan Bai; Kun Song; Chen Zhou; Yuping Gao; Xiaochun Lu; Shougang Zhang (Satellite Navigation)
Abstract The development of precise time synchronization technology is key to the effective application of time–frequency standards. It will significantly promote the application of precise time–frequency standards in the areas such as Positioning, Navigation, and Timing, lunar navigation, and cutting-edge fundamental physics research. This study presents an improved carrier-phase-based method for time synchronization, which was demonstrated through both laboratory and satellite-ground experiments via the China Space Station (CSS)-ground synchronization system. Initial laboratory experiments confirmed the system’s stability, achieving picosecond-level accuracy, highlighting the robustness of the method in controlled environments. Then, preliminary satellite-to-ground synchronization experiments were conducted using the CSS and ground stations, validating the effectiveness of the carrier-phase-based method. The time synchronization accuracy reached the picosecond-level, significantly surpassing traditional pseudocode techniques, which typically achieve sub-nanosecond level accuracy. Additionally, the Allan Deviation results indicated an improvement in stability by about an order of magnitude compared to traditional pseudocode-based methods. This demonstrates that the carrier-phase-based method can effectively mitigate common sources of system errors and enhance time synchronization capabilities. Therefore, this method can provide an effective technical reference for future applications requiring higher precision in time synchronization.